2019
DOI: 10.1007/s10029-019-01979-9
|View full text |Cite
|
Sign up to set email alerts
|

A systematic methodological review of non-randomised interventional studies of elective ventral hernia repair: clear definitions and a standardised minimum dataset are needed

Abstract: Background Ventral hernias (VHs) often recur after surgical repair and subsequent attempts at repair are especially challenging. Rigorous research to reduce recurrence is required but such studies must be well-designed and report representative and comprehensive outcomes. Objective We aimed to assesses methodological quality of non-randomised interventional studies of VH repair by systematic review. Methods We searched the indexed literature for non-randomised studies of interventions for VH repair, January 19… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 67 publications
(146 reference statements)
0
10
0
1
Order By: Relevance
“…Despite this, the majority of studies fail adequately to capture or report patient-centred outcomes such as quality of life and pain. Parker and colleagues reported that four studies out of 31 employed a PRO as a primary endpoint in RCTs assessing ventral hernia repair 6 . To ensure outcome reporting reflects the goals and aims of incisional hernia repair, it is essential that PROs are appropriately defined, captured and reported.…”
Section: Introductionmentioning
confidence: 99%
“…Despite this, the majority of studies fail adequately to capture or report patient-centred outcomes such as quality of life and pain. Parker and colleagues reported that four studies out of 31 employed a PRO as a primary endpoint in RCTs assessing ventral hernia repair 6 . To ensure outcome reporting reflects the goals and aims of incisional hernia repair, it is essential that PROs are appropriately defined, captured and reported.…”
Section: Introductionmentioning
confidence: 99%
“…There were differences in the detection of recurrence methods employed (clinical versus radiological (ultrasound versus cross-sectional imaging e.g. computed tomography) versus combination), although five studies failed to describe the detection method used [ 11 , 13 , 16 , 18 , 22 ]. Several studies included a mixture of mesh placements within their cohorts making it difficult to draw meaningful conclusions from the results.…”
Section: Discussionmentioning
confidence: 99%
“…Descriptions of procedures performed were collected including surgical technique, number of procedures previously performed by the surgeon and monitoring of technique. Degree of contamination (clean contaminated, contaminated, and dirty surgery) was defined according to the Centre for Disease Control Surgical Wounds Classification [ 11 ] and location of bioabsorbable mesh placement was also evaluated: intraperitoneal, preperitoneal, retro-muscular, retro-rectus, inlay, or onlay [ 12 , 13 ]. Urgency of surgery (i.e.…”
Section: Methodsmentioning
confidence: 99%
“…Matching is also sometimes used. In the methodological study of non-randomized interventional studies of elective ventral hernia repair, Parker et al matched prospective studies with retrospective studies and compared reporting standards [74]. Some other methodological studies use statistical adjustments.…”
Section: Some Frequently Asked Questions About Methodsological Studiesmentioning
confidence: 99%